ANALISIS HASIL UJI KOMPETENSI DI LEMBAGA SERTIFIKASI PROFESI OTOMOTIF INDONESIA SE-DAERAH ISTIMEWA YOGYAKARTA TAHUN 2017 - Rendra Ananta Prima Hardiyanta; Moch. Solikin (Jurnal Pendidikan Vokasi Otomotif, 2019)
This study aims to: (1) know competence test results of competency test participants in the Indonesian Automotive Profession Certification Body from Yogyakarta Special Region (DIY) in 2017 if reviewed from the certification scheme and (2) to know the distribution of competency unit of competency test participants causing competency test participants to be declared not yet competent in LSP Otomotif Indonesia from DIY in 2017 This research is a descriptive research. The subject in this research is 198 competency test participants. Technique of collecting data is documentation. This research uses quantitative analysis technique. The result of the research shows that: (1) the competency test results of competency test participants from the Special Region of Yogyakarta in Indonesian Automotive Profession Certification Body in 2017 if reviewed based on scheme 01 (Service Maintenance 5000 KM Motorcycles) is 70% (70) participants are declared competent and 30% (30) participants are deemed incompetent (including high category). Furthermore, in scheme 02 (Service and Maintenance 10,000 Km of Conventional Light Vehicles) 75% (15) are competent and 25% (5) declared incompetent (including category and in scheme 03 (Service and Maintenance of 10,000 Km Light Vehicle Injection System) of 61.54% (48) participants are declared competent and 38.46% (30) declared not yet competent (including very low category), (2) the distribution of competency units shows that in scheme 01, competency unit that most competent participant is OTO.SM02.001.01 (Maintaining Engine with its Components) that is equal to 73.33%, in the scheme of 02 competency units that most participants are not competent are OTO.KR02.014.01 (Maintenance / Service of Gasoline Fuel System) and OTO.KR05.011.01 (Fixing Ignition System) that is equal to 100% , whereas in the scheme of 03 competency unit that most participants are not competent is OTO.KR05.012.01 (Maintaining / Servicing and Improving Engine Management system) that is equal to 76.67%.